The Use of Cooperative Integrated Reading and Composition Method for Better Quality Writing of Middle School Students - Nadia Nadia (Universitas Syiah Kuala, 2016)
This study was intended to find out whether the Cooperative Integrated Reading and Composition (CIRC) method would be effective for improving the quality of writing in English for second grade students in a middle school in Jakarta. The major purpose for doing this research was to find out whether students in a class taught using the CIRC method would produce better writing, especially recount texts, than students taught with the Grammar Translation Method (GTM). The subjects for this study were the students in a class as the experimental group (EG) and another class as the control group (CG). These classes were chosen to ensure the homogeneity of the participants. To find out the effectiveness of the CIRC method, pre-tests and post-tests were given to all the students in those groups. Data analysis of the results showed that there was a significant difference in the mean scores from the post-test results from the two groups. The mean score of the post-tests from the EG was higher than that from the CG, that is 61 to 39, while the gained score for the t-test was 5 and the value for t-table was 1.68 at a level of significance of 0.05. Hence it can be concluded that the students who were taught using the CIRC method had better performances in writing recount texts than those who were not. In brief, the CIRC method resulted in a better quality of writing by students and gave a positive effect for the teaching-learning process.